2020
DOI: 10.1016/j.psj.2020.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding frequency on the growth performance, carcass traits, and apparent nutrient digestibility in geese

Abstract: This study was conducted to determine the effect of feeding frequency on growth performance, carcass traits, and apparent nutrient digestibility in geese from 28 to 70 D of age. In experiment 1, a total of 240 geese were distributed in a completely randomized design into 4 treatments and 6 replicates of 10 birds each. The treatments were free access to the feeder (ad libitum) and access to the feeder 3, 4, and 5 times daily. Geese fed 3 times daily had a lower ( P < 0.05) BW, ADG, and AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Its meat is rich in unsaturated fatty acids and essential fatty acids as well as low cholesterol, and provides the high-quality protein for humans ( Schmid, 2011 ). Hence, there is a growing interest in improving worldwide goose production ( Liu et al., 2020 ). In 2020, more than 700 million geese were used globally for meat production and about 86% of them are from China ( Hou and Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its meat is rich in unsaturated fatty acids and essential fatty acids as well as low cholesterol, and provides the high-quality protein for humans ( Schmid, 2011 ). Hence, there is a growing interest in improving worldwide goose production ( Liu et al., 2020 ). In 2020, more than 700 million geese were used globally for meat production and about 86% of them are from China ( Hou and Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apparent digestibility was determined using the total feces collection method [ 15 ]. After the end of the feeding experiment period, 8 laying hens were randomly selected from each group to be unfed for 2 days to empty the original feces in the intestines, then re-fed for 2 days and had their feces collected for 4 consecutive days after feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Aziz and Masoud [15] reported no significant differences in overall weight, average daily gain and feed conversion ratio among chickens with one feed, 2 equal feeds and 3 equal feeds per day. Furthermore, Liu et al [16] demonstrated that geese fed ad libitum, thrice, 4 and 5 times per day had no significant difference on final BW, average daily gain and feed efficiency. They suggested all feeding regimes were suitable for geese to achieve optimal production [16].…”
Section: Introductionmentioning
confidence: 99%